HUBUNGAN MU’TAZILAH DENGAN KALAM DAN PERANNYA DALAM SEJARAH PEMIKIRAN ISLAM - Yesi Ulandari; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Mu'tazilah is one of the theological schools in Islam that emerged in the 8th century AD. This school is known for its emphasis on rationality and logic in understanding religious teachings. The relationship of Mu'tazilah to kalam, which is the science of theological argumentation, is very significant, because Mu'tazilah played a pioneering role in the development of the kalam method. They attempted to explain and defend Islamic beliefs through rational argumentation, touching on issues such as God's justice, His attributes, and human freedom. The role of Mu'tazilah in the history of Islamic thought cannot be separated from their contribution in forming philosophical and theological dialogue. They attempted to bridge the gap between revelation and reason, emphasizing that human reason can be used to understand religious truths. In this context, Mu'tazilah developed important concepts such as tawhid (the oneness of God), adalat (God's justice), and al-wa'd wa al- wa'id (promise and threat). Although this school declined in influence after the 10th century, Mu'tazilite thought continued to have a profound impact on the Islamic intellectual tradition and influenced many subsequent theological schools. Thus, the Mu'tazilites are not only an important part of the history of Islamic theology, but also show how rationality can interact with faith in a spiritual context